THESEUS AND THE MINOTAUR - Gkoutzouri, Anna (Amersham, Buckinghamshire : Faros Books, 2020)
Even the very young can now learn about the great Greek hero Theseus, while playing with five different mechanisms and enjoying the colourful, vivid illustrations.
First published 2019 by Papadopoulos Publishing, Greece.
On board pages.
From 18+ months
Translated from the Greek.
Keywords: Theseus, -- King of Athens -- Juvenile literature; Minotaur -- (Greek mythological character) -- Juvenile literature; Heroes -- Juvenile literature; Board books; Toy and movable books; Myths